Closing the knowledge gap in Irish manufacturing - a north-south comparison - Nola Hewitt-Dundas; Stephen Roper (European Regional Science Association (ERSA), 2002)
Knowledge, however defined, is perceived as firms "key" source of competitive advantage and a central determinant of productivity and wealth creation. The value of knowledge as a competitive asset is not intrinsic, but depends instead on its application, i.e. innovation or the transformation of knowledge into new technologies, products and, or services. Therefore, the extent of innovation within an economy depends crucially on the rapid diffusion of new technology and best practice, which it is argued depends in turn on building strong regional networks. So, knowledge, its distribution and diffusion - particularly through the supply chain - form the central focus of this paper. For some economies (e.g. Finland, Israel) with high levels of domestic R&D spending much of the 'new' knowledge driving local business competitiveness is created domestically. For Ireland, both North and South, however, historically low levels of domestic R&D spending mean that inward technology transfer - primarily associated with inward investment - has been crucial to recent economic development. This suggests two main questions. First, how does the knowledge transferred to Ireland, North and South, through international inward investment compare to international best practice? And, second, to what extent does this knowledge then diffuse to other manufacturing businesses located in Ireland? A third, and related, question concerns the contrasting experiences of Ireland, North and South, particularly given the very different history of inward investment in the two areas. The analysis in the paper is based on data collected through face-to-face interviews with 94 Multi-national enterprise (MNE) plants in the South and North of Ireland. The relatively high response rates achieved and the fact that the final sample coverage resembles relatively closely that of the underlying population suggests that the sample is likely to provide results which are representative of the whole population of large MNE plants in both the South and North of Ireland. The research findings demonstrate that the potential to transfer knowledge from MNE plants to local firms through the supply chain is higher in the South of Ireland than in the North. Yet, Northern suppliers' adoption of a range of best practice techniques lags further behind their MNE plants than in the South. Therefore, larger average knowledge gaps suggest a greater potential benefit from knowledge transfers in the North of Ireland. Yet, while general contact as part of normal trading relations between MNE plants and their suppliers is more common in the North, contact in the South of Ireland is characterised by developmental interactions such as collaboration on product developments and quality assurance systems. Furthermore, southern MNE plants report having had a significantly greater impact on both the performance and the competitiveness of local suppliers than their Northern counterparts.
Keywords: 330